Breast Milk Stem Cell Survival in Neonate's Gut, Entery into Neonate Circulation and Adaption by the Body - Ghosh, Amit (Current Stem Cell Research & Therapy, 2020)
The stem cell exchange during pregnancy is thought to remain chimeras for life. Few studies recently revealed that maternal transfer of viable stem cells to the offspring continues even after birth during breastfeeding. Some of these stem cells are likely to be integrated into different organs (brain, blood, kidneys, and pancreas) including neurons and insulin-producing cells in the pancreas to become functional cells. This finding opens a new avenue for research on therapeutic uses of breast milk- derived stem cells. Recently Dr. Foteini Hassiotou used glowing mice, which were genetically modified to express a gene called tdTomato that causes cells to appear red under fluorescence light. These mice were mated, and their babies were swapped with the pups of another, unmodified mother mouse. The new pups suckled the modified mouse and, as a result, obtained glowing red stem cells from breast milk. The study has never been replicated in humans, so it is not clear yet if the findings apply to humans as in the case of mice. However, the results of the study are the jumping-off points for future research on human breast milk stem cells and their possible application in stem cell therapies. Additional studies are necessary to understand the passage of human breast milk stem cells through the neonate’s GI tract, and passage to the systemic circulation.
Keywords: colostrum